THE SIGNIFICANCE OF SCIENCE COMMUNICATION IN INDIAN NEWS PUBLICATIONS: A DECADE OF DISSEMINATING DISCOVERIES AND INVENTIONS (CAHIERS MAGELLANES-NS, 2024)
Science communication plays a crucial role in disseminating information about new discoveries and inventions, significantly impacting the quality of life for citizens. This paper analyzes Indian news publications from the last ten years to demonstrate the importance of science communication. By examining the portrayal of scientific advancements and their societal implications, we highlight the role of science in enhancing public understanding, driving policy changes, and improving everyday life. Through a comprehensive review of news articles and relevant citations, we underscore the transformative power of effective science communication in India.